2016
DOI: 10.18632/oncotarget.12773
|View full text |Cite
|
Sign up to set email alerts
|

Secreted protein acidic and rich in cysteine (SPARC) induces lipotoxicity in neuroblastoma by regulating transport of albumin complexed with fatty acids

Abstract: SPARC is a matrix protein that mediates interactions between cells and the microenvironment. In cancer, SPARC may either promote or inhibit tumor growth depending upon the tumor type. In neuroblastoma, SPARC is expressed in the stromal Schwannian cells and functions as a tumor suppressor. Here, we developed a novel in vivo model of stroma-rich neuroblastoma using non-tumorigenic SHEP cells with modulated levels of SPARC, mixed with tumorigenic KCNR cells. Tumors with stroma-derived SPARC displayed suppressed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Previous studies have shown a correlation between SPARC and HSA at the protein expression level in cancer cells and possible implications for the therapeutic effect but did not show a direct relationship of SPARC in HSA accumulation in tumors 32. Another study showed the binding affinity between bovine serum albumin (BSA) and SPARC, and its internalization using a non-cancer cell line and suggested that HSA may have a similar affinity to SPARC 33. Therefore, it was necessary to identify HSA and SPARC interactions in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown a correlation between SPARC and HSA at the protein expression level in cancer cells and possible implications for the therapeutic effect but did not show a direct relationship of SPARC in HSA accumulation in tumors 32. Another study showed the binding affinity between bovine serum albumin (BSA) and SPARC, and its internalization using a non-cancer cell line and suggested that HSA may have a similar affinity to SPARC 33. Therefore, it was necessary to identify HSA and SPARC interactions in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…BSA and SPARC binding was determined using IP methods following the previously published procedure 33. For the pre-clearing step, we incubated 10 μg of HSA, 4.76 μg/mL of normal rabbit serum (X0902, Dako, Santa Clara, CA), and 20 μl of protein A/G PLUS-Agarose (sc-2003, SCB) in a test tube for 1 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…SPARC is a widely expressed profibrotic protein with pleiotropic roles, which have been studied in a variety of conditions (18,19). Previous evidence has demonstrated that SPARC was associated with human obesity and diabetes (11).…”
Section: Discussionmentioning
confidence: 99%
“…SPARC is a secreted protein that binds albumin (albumin-binding protein) and is highly expressed in many cancers. Some studies have proposed the involvement of SPARC in the uptake of albumin in tumors ( Frei, 2011 ; Liu et al, 2015 ; Chlenski et al, 2016 ; Park et al, 2019 ) and in NPs internalization via HSA in cancer cells ( Hoang et al, 2015 ). Thanks to this feature, SPARC represents a good molecular target for the active NPs delivery.…”
Section: Resultsmentioning
confidence: 99%
“…It is the most abundant plasma protein in human blood with a molecular weight of 66.5 kDa and a molecular size of ∼7.2 nm and has been already explored as a useful medical device for therapeutic and diagnostic agents delivery, due to its non-immunogenicity and nontoxicity ( He and Carter, 1992 ; Bairagi et al, 2015 ; Mehtala et al, 2015 ). Moreover, albumin interacts with cellular receptors that include glycoproteins Gp60, Gp30, and Gp18 and the secreted protein acidic and rich in cysteine (SPARC), and these interactions can be used for a specific targeted delivery of NPs ( Schnitzer, 1992 ; Tiruppathi et al, 1996 ; Desai et al, 2009 ; Chlenski et al, 2016 ). Particular interest among albumin binding proteins is attracted by SPARC, which is overexpressed in the extracellular matrix and in various cancer cells and is associated with tissue growth and cell proliferation.…”
Section: Introductionmentioning
confidence: 99%